Kesadaran Orang Tua Bagi Peningkatan Kualitas Pendidikan Agama Islam Anak Keluarga Petani - Ba'agil, Rahmad (Pascasarjana UIN ANTASARI Banjarmasin, 2022)
One of the phenomena of poverty that occurs in this community is in Barito Kuala which is one of the rice granaries in South Kalimantan, namely in Anjir Pasar Lama village, Anjir Pasar district. The role of parents with backgrounds in Anjir Pasar Lama Village in Islamic religious education can be done to ensure that children start from TKA/TPA Al Quran in Anjir Pasar Lama Village, take their children to the local Koran teacher and visit the Taklim assembly, even though have to travel quite a distance. Determination of data sources in this study is to use purposive sampling, namely: selected people who will be asked questions, and the questions according to the specific characteristics of the sample, purposively until the data collected is deemed sufficient. The family as one of the centers of education can be said to be still not maximized due to the feelings of parents who feel they are not 'worthy' or marginal. In addition, the intention of parents to send their children to a higher level tends to be non-existent. This is because parents are